KARAKTERISTIK CAMPURAN SEMI FLEXIBLE PAVEMENT DENGAN MENGGUNAKAN ADDITIVE VISCOCRETE-10 PADA MORTAR DAN GILSONITE PADA ASPAL DITINJAU DARI UJI KUAT LENTUR - Iwayan Dermana (JURNAL PLANOLOGI DAN SIPIL (JPS), 2019)
Road pavement damage within its service period has always been a problem of land transportation. The pavement failure to bear the load is one of the decreasing factors to the pavement durability. It is important to select the appropriate pavement to anticipate such problem. Commonly used pavement types (stiff and flexible pavement) have their strengths and weakness. Innovation and technology development are required to obtain better pavement. One of the efforts was developing the semi-flexible pavement by combining the current pavement strengths. Therefore, the researcher attempted to study the semi flexible pavement characteristics using the viscocrete-10 additive in mortar and Gilsonite in asphalt reviewed by flexural strength test. Research was carried out by composing the open graded asphalt (OGA) specimens in beam shape with asphalt concentration of 2.5%, 3.0%, and 3.5% and added with 0.3% Gilsonite additive. The OGA beam shaped was grouted with mortar cement using the additive viscocrate-10 concentrations of 0.8%, 0.9% and 1.0% to become the semi flexible pavement specimen. Next, the 28 days specimen was tested for its flexural strength using the method of 4 loading points. Analysis of the specimen strength and flexural test under the maximum load was taken to the specimen. Results of the research showed that the deflection and flexural strength varied in accordance to the increasing addition of asphalt as well as viscocrete-10 concentration. The highest value of the flexible strength, which was 3.32 MPa, was achieved by the specimen with asphalt and viscocrete additive concentration of 2.5% and 0.8%, respectively. The highest flexural strength value, which was 3.60mm, was obtained by the specimen with 3.5% asphalt content and 1.0% viscocrete-10 content. The test taken to the comparing specimen, which was the deflection pavement (SMA 0/11) showed 1.19MPa and 11.3 mm flexural strength. The stiffness test (normal concrete) indicated that the bending strength was 4.6 MPa with 1.53 mm flexural strength.